Drug Repurposing in Anticancer Reagent Development - Chen, Peng-chen; Liu, Xaiolong; Lin, Yao (Combinatorial Chemistry & High Throughput Screening, 2017)
Background: Cancer is a complex disease and a huge threat to human health. The prognosis for some cancer types such as breast cancer has improved dramatically over the past 50 years due to rapid development of surgery, chemotherapy and radiotherapy technologies. However, for many patients bearing unresectable cancers, the prognosis remained poor. For this reason, there is always high demand for newer and better therapeutic reagents in cancer field. But the development of anticancer drugs is risky, lengthy and costly. Not many new anticancer reagents come into market every year. Objective: This review focuses on the latest progress of chemotherapy drug repurposing in cancer research. Conclusion: It is clear from the review of that drug repurposing is faster and cheaper than conventional drug development process. The anticancer efficacy of numerous non-cancer drugs are being tested now. However, not many of them have obtained enough evidence to go into clinical trials for cancer treatment. How to filter the right candidate and narrow the gap between bench and bed remains a hurdle for both conventional and repurposing drug development.
Keywords: signaling pathway